Mauritius von Craûn / - Reinitzer, Heimo (De Gruyter, 2000)
This Middle High German text tells the story of positive and negative knightly deeds from the Trojan Wars to the 'present' (around 1200). In the story the exemplary character of the Christian code of chivalry is challenged by a knightly ideology making chivalrous 'performance' dependent on amorous favours. The unrightful matrimonial compact between the Countess of Beamunt and Sir Mauritius von Craûn culminates in a 'fulfillment' that creates an irreconcilable rift between the parties to the agreement. The amusing text, handed down to us solely in the early 16th century »Ambraser Heldenbuch«, is given here in a reconstructed Middle High German form corresponding to the language of 1200 but adhering as closely as possible to the manuscript. Metric considerations were left out of account in the text production. The edition also contains the text of an Old French fable on a comparable subject, complete with a translation into New High German.
10.1515/9783110935936
Keywords: Deutsche Literatur.; POETRY